Pengaruh Selulosa Mikrokristal Kulit Buah Kapuk Terhadap Laju Disolusi Tablet Furosemida - Putri Handayani; Juanita Tanuwijaya; Karsono Karsono* (Journal of Pharmaceutics and Pharmacology, 2012)
Background: Kapok pericarpium (Ceiba petandra (L.) Gaertner) contain 94.04% α-cellulose. Microcrystalline cellulose is used as diluent in formulation of direct compression. Direct compression is the most efficient and economic technique for tablet manufacturing process. Objective: This study was conducted to determine the influence of microcrystalline cellulose obtained from kapok pericarpium (C. petandra (L.) Gaertner) on the dissolution of furosemide tablet. Methods: α-cellulose was isolated by removing lignin and hemicelluloses from kapok pericarpium (C. petandra (L.) Gaertner). Microcrystalline cellulose from kapok pericarpium (C. petandra (L.) Gaertner) was obtained by controlled hydrolysis α-cellulose with HCl 2.5 N. Furosemide tablets were prepared using microcrystalline cellulose from kapok pericarpium (C. petandra (L.) Gaertner) (F1) and Avicel® PH 102 (without microcrystalline cellulose from kapok pericarpium (C. petandra (L.) Gaertner) (F2). Tablets were made by direct compression. Furthermore, tablets were evaluated including tablet hardness, disintegration time, content uniformity, and dissolution test using pH 5.8 phosphate buffer solution, with paddle method, then the concentration of furosemide was determined by UV spectrophotometric with F2 was used as reference. Results: The yield of microcrystalline cellulose from kapok pericarpium (C. petandra (L.) Gaertner) was 16.38%. The results of furosemide tablets evaluation including tablet hardness of F1 = 7.40 kg and F2 = 7.45 kg; disintegtation time of F1 = 17 seconds and F2 = 12 minutes 29 seconds; content uniformity of F1 = 98.87% ± 0.02% and F2 = 102.41 ± 0.05%. The result of dissolution test showed that the 85% of cumulative percentage for F1was reached at 30th minute and for F2 at 60th minute. Conclusion: Furosemide tablet which used microcrystalline cellulose obtained from kapok pericarpium (C. petandra (L.) Gaertner) as diluent meets the requirements of furosemide tablet dissolution contained in 4th Edition of Indonesian Pharmacopeia. Keywords: microcrystalline cellulose, kapok, direct compression tablet, dissolution test ABSTRAK Latar Belakang: Kulit buah kapuk (Ceiba petandra (L.) Gaertner) mengandung α-selulosa 94,04%. Selulosa mikrokristal digunakan sebagai bahan pengisi dalam formula tablet cetak langsung. Metode cetak langsung merupakan metode yang paling efisien dan paling ekonomis untuk memproduksi tablet. Tujuan: Penelitian ini adalah untuk mengetahui pengaruh selulosa mikrokristal kulit buah kapuk (C. petandra (L.) Gaertner) (SMKBK) terhadap disolusi tablet furosemida. Metode Penelitian: Isolasi α-selulosa dilakukan dengan menghilangkan lignin dan hemiselulosa dari kulit buah kapuk (C. petandra (L.) Gaertner). Selulosa mikrokristal dari kulit buah kapuk (SMKBK) diperoleh dengan menghidrolisis α-selulosa dengan HCl 2,5 N. Formula tablet furosemida yang dibuat yaitu formula dengan bahan pengisi SMKBK (F1) dan dengan bahan pengisi Avicel® PH 102 (tanpa SMKBK) (F2). Pembuatan tablet dilakukan dengan metode cetak langsung. Selanjutnya, tablet dievaluasi meliputi uji kekerasan tablet, waktu hancur, keseragaman sediaan, dan uji disolusi menggunakan medium larutan dapar fosfat pH 5,8, dengan metode dayung, kemudian penetapan kadar furosemida dengan spektrofotometri UV dengan F2 sebagai pembanding. Hasil: Rendemen SMKBK adalah 16,38%. Hasil evaluasi tablet furosemida meliputi kekerasan tablet F1 = 7,40 kg dan F2 = 7,45 kg; waktu hancur F1 = 17 detik dan F2 = 12 menit 29 detik; keseragaman sediaan F1 = 98,87% ± 0,02% dan F2 = 102,41 ± 0,05%. Hasil uji disolusi menunjukkan pencapaian 85% persen kumulatif untuk F1 pada menit ke-30, sedangkan F2 pada menit ke-60. Kesimpulan: Tablet furosemida menggunakan selulosa mikrokristal kulit buah kapuk (C. petandra (L.) Gaertner) memenuhi persyaratan uji disolusi tablet furosemida yang terdapat dalam Farmakope Indonesia Edisi IV. Kata kunci: selulosa mikrokristal, kapuk, tablet cetak langsung, uji disolusi Korespondensi penulis: karsonobk50@yahoo.com